NEEDS ANALYSIS: THE POTENTIAL ROLE IN EAP PRE-SESSIONAL COURSE DESIGN - Purnamasari, Asri (PEOPLE: International Journal of Social Sciences, 2020)
The purpose of this research is to analyse the potential role of needs analysis in the process of English for Academic Purposes pre-sessional course design for English-medium university student candidates in Indonesia. Based on relevant literature about the nature of needs analysis related to learners’ descriptions and their context, the contribution of needs analysis on course design/implementation is discussed. The paper considers learning-centred approaches as an appropriate way to define learners’ needs in the process of negotiating the meaning, deciding what will be achieved, and how the learners learn, especially for English-medium university student candidates in Indonesia. By having these steps, the EAP course could be developed in accordance with learning objectives of every group of learners. Finally, a plan of conducting a needs analysis through questionnaires implemented for the learners before designing the programme is described. The result of the needs analysis conducted could benefit some institutions, instructors, and the learners in designing their EAP courses.